On the Allocation of Competences between the European Union and its Member States in the Media Sector | Zur Kompetenzverteilung zwischen der Europäischen Union und den Mitgliedstaaten im Mediensektor An Analysis with particular Consideration of Measures concerning Media Pluralism | Eine Untersuchung unter besonderer Berücksichtigung medienvielfaltsbezogener Maßnahmen - Cole, Mark D. (2021)
With a special focus on safeguarding media pluralism, this study sheds light on the allocation of competences between the EU and the Member States in the media sector. Not only is the primary and secondary legal framework analysed in detail, but the relevant elements for ensuring media pluralism at EU level and core problems in media regulation under public international law are also examined. The study identifies both existing and potential tensions between national and EU level as well as limits to EU regulatory action. The analysis is put into context with the EU Digital Services Act Package and concludes with the identification of policy options for Member States.